Receiving more: Utopia in Spain and new Spain - Kern, D. (The Oxford Handbook of Thomas More's Utopia, 2023)
Keywords: dept.his

Book Review: Edington, Claire E. – Beyond the Asylum: Mental Illness in French Colonial Vietnam. - Thompson, C. Michele (Histoire sociale / Social History, 2023)
Keywords: book.review; dept.his

The Duke of Lennox, 1574 1624: A Jacobean Courtier s Life. David Bergeron. Edinburgh: Edinburgh University Press, 2022. x + 244 pp. $110 - Kern, Darcy (Renaissance Quarterly, 2023)
Keywords: book.review; dept.his

The many currents of antebellum maritime empire - Smith, Jason W. (Diplomatic History, 2023)
Keywords: dept.his; peer-reviewed

Costa Rica after Coffee: The Co-op Era in History and Memory - Kordick, Carmen (Agricultural History, 2023)
Keywords: book.review; dept.his

Aspects of Greek-Russian Relations in the Early Modern and Modern Periods (17th-20th Centuries) - Chrissidis, Nikolaos (Annuaire de l'École pratique des hautes études (EPHE), Section des sciences religieuses. Résumé des conférences et travaux, 2023)
This series of four presentations sought to examine case studies of Greek-Russian relations in the early modern and, mostly, modern period. In the choice of topics, I was guided by two considerations: first, I sought to highlight topics that, to my mind, have not yet attracted the attention they deserve in historiography. For example, although alms collections in the Russian Empire in the early modern period have been discussed repeatedly, this has not been the case until quite recently for t...
Keywords: Christianisme orthodoxe; Histoire des chrétiens d’Orient (XVIe-XXIe siècle); dept.his

Russia in the German global imaginary: imperial visions and utopian desires, 1905-1941 - Paddock, Troy (First World War Studies, 2023)
Keywords: book.review; dept.his

Islam on the Margins: Studies in Memory of Michael Bonner - Judd, Steven; Haug, Robert (BRILL, 2023)
Islam on the Margins commemorates the contributions Michael Bonner made to Near Eastern Studies. It consists of fourteen contributions by his students and colleagues that focus on various aspects of his work. The contributions coalesce around four major themes of Bonner’s endeavours: Holy War and the Frontier, Qurʾan and Law, Geography and Ethnography, and Books, Coins and Titles. Collectively, the contributions underscore the breadth of Michael Bonner’s erudition and impact on the field.
Keywords: History / Asia / General; History / Middle East / General; Religion / Islam / General; dept.his

The Cassock Does Not a Monk Make. Or Does It? Fake and Real Monks from the Orthodox East in the Russian Empire (19th — Early 20th Сentury) - Chrissidis, Nikolaos (Istoriya, 2023)
Monastic tonsure of citizens of the Russian Empire abroad became a particularly complex issue during the latter half of the nineteenth century, when Mt. Athos became a favorite destination of those interested in assuming the monastic habit outside the empire. The Russian authorities sought to control and regulate such tonsures by establishing procedures for checking their validity, and by ruling out automatic recognition of them in the empire. Individuals who were tonsured as monks abroad manipulated or tried to manipulate such regulations in order to facilitate travel back and forth from the Russian Empire for their own purposes. The result was that the real and apparent ambiguities that such rules allowed for were exploited by both state authorities and by real or fake monks themselves. The essay seeks to offer some perspectives on this phenomenon by focusing on four cases preserved in archival records. © 2023 Ltd "Integration: Education and Science". All rights reserved.
Keywords: Mount Athos; St. Panteleimon Monastery; dept.his; fake monks; monasticism; peer-reviewed; tonsures abroad

The Khārijites in Early Islamic Historical Tradition: Heroes and Villains. By HANNAH-LENA HAGEMANN. Edinburgh: EDINBURGH UNIVERSITY PRESS, 2021. Pp. xii + 316. $110, £85 - Judd, Steven C. (Journal of the American Oriental Society, 2023)
Keywords: book.review; dept.his